Literature Review: Policy Analysis on Exclusive Breastfeeding for Working Mothers: Tinjauan Pustaka: Analisis Kebijakan Pemberian ASI Eksklusif bagi Ibu Bekerja - Husnul Khotimah; Dumilah Ayuningtyas (Jurnal Obstretika Scientia, 2024)
Exclusive breastfeeding is an important part of fulfilling infant nutrition to achieve optimal growth and development in early life and subsequent growth. Some mothers cannot provide exclusive breastfeeding, especially working mothers. The purpose of this study was to analyze health policies on providing exclusive breastfeeding to working mothers. This study is a systematic review conducted in 2024 which was taken from the search site "google scholar". The articles selected after going through the process of identification, screening and determining the inclusion criteria were 9 articles. Working mothers face major challenges in providing exclusive breastfeeding to their babies. This challenge arises because of the conflict between work and family demands, busy work schedules, lack of flexibility, and inadequate lactation facilities in the workplace are the main obstacles, lack of social support from the surrounding environment also exacerbates the situation, stress due to work and family demands can affect breast milk production and make mothers feel uncomfortable while breastfeeding. However, with strong support from various parties, such as companies, families, and communities, working mothers can overcome these challenges and continue to provide exclusive breastfeeding. Comprehensive solutions are needed to address this complex problem, such as providing adequate lactation facilities, company policies that support breastfeeding, and socialization about the importance of exclusive breastfeeding.